2020
DOI: 10.1089/rej.2019.2225
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characterization of Prolonged Normothermic and Cold Cerebral Ischemia in the Adult Rat

Abstract: The ultrastructural effects of prolonged normothermic and cold ischemia on the cerebral cortex of the adult rat were investigated. Complete cerebral ischemia was produced by cardiac arrest and the animals' temperature was maintained at 37°C for periods ranging from 0 to 81 hours before electron microscopy preparation. Electron micrographs of cold cerebral ischemia were generated after stabilizing the rat's temperature at 0°C after cardiac arrest for periods ranging from 0 hours to 6 months. A qualitative exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Environmental conditions influence postmortem changes. In the present study, the onset and progression of these changes was notably slower in animals stored under refrigeration in contrast with animals stored at room temperature, corroborating the positive effect of refrigeration in delaying postmortem changes (46)(47)(48). Overall, severity of findings after 48 h at room temperature was higher than after seven days under refrigeration and similar to or slightly lower than after 14 days under refrigeration, confirming that higher environmental temperatures accelerate the progression of autolytic changes.…”
Section: Discussionsupporting
confidence: 84%
“…Environmental conditions influence postmortem changes. In the present study, the onset and progression of these changes was notably slower in animals stored under refrigeration in contrast with animals stored at room temperature, corroborating the positive effect of refrigeration in delaying postmortem changes (46)(47)(48). Overall, severity of findings after 48 h at room temperature was higher than after seven days under refrigeration and similar to or slightly lower than after 14 days under refrigeration, confirming that higher environmental temperatures accelerate the progression of autolytic changes.…”
Section: Discussionsupporting
confidence: 84%
“…h, but the ability to visualize them was lost by a PMI of 24 h (de Wolf et al, 2020). When stored at 0 °C, this study found that synapses could be visualized at 48 h of PMI but were lost at the next time point studied of 168 h of PMI.…”
Section: Synapsesmentioning
confidence: 76%
“…Hukkanen 1987 note the formation of network-like structures in myelin lamellae at 24 h (Hukkanen and Röyttä, 1987). de Wolf 2000 notes unravelling of myelin sheaths at 9 h PMI with storage at 37 °C (de Wolf et al, 2020). Ansari 1976b notes that myelin lamellae splitting can also occur in cerebral edema and that its occurrence may be associated with the postmortem increase in the water content of the brain (Ansari et al, 1976b).…”
Section: Myelinmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue of RR contains a comprehensive study to understand the ultrastructural effects of circulatory arrest on the mammalian brain. 4 The authors of this article show that ischemia-induced damage to the brain is a time-and temperature-dependent process. It takes many hours of normothermic global ischemia, and several weeks of cold global ischemia, to damage the fine structure of the brain to a degree that the original structure of the brain cannot be recognized or inferred.…”
mentioning
confidence: 96%